f (x) = 4+2x+3e^x
f −1(7) = ?
and
f (x) = 6x^3 +3x+5
g(x) = f −1(x)
g(x) = ?
Any help would be greatly appreciated. Thanks.
For the first, there is no simple formula for the inverse of such a function, so you are looking for a numerical answer. It might help you to plot the function and get an estimate for a possible answer, then try verifying the answer you've guessed: it's almost a trick question.
For the second, there is a general formula for the solution of a cubic, but are you sure that was what you're being asked here?